The Role of Cibinong Class IIA Correctional Facility in Preventing Recidivism - Afdal, Muhamad; Hartini, Sri; Fajri, Ibrahim (JURNAL MAHASISWA YUSTISI, 2025)
This study examines the efforts of the Cibinong Class IIA Correctional Facility in preventing recidivism among inmates through structured rehabilitation and reintegration programs. The research employs a juridical-empirical approach, utilizing qualitative data from primary sources such as interviews and observations, and secondary sources including legislation and prior studies. Results indicate that while the facility employs diverse programs aimed at rehabilitation, challenges such as overcrowding, limited resources, and societal stigma impede its effectiveness. Recommendations for improvement include enhanced funding, public education on reintegration, and increased collaboration with external stakeholders.